2022
DOI: 10.3390/ani12030247
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Intraoperative Gastro-Oesophageal Reflux in Dogs and Cats

Abstract: In animals, gastro-oesophageal reflux (GOR) may occur during anaesthesia, and it can lead to severe consequences such as oesophagitis and oesophageal stricture. This systematic review investigates the effect of fasting duration and anaesthetic and nonanaesthetic drugs on GOR in dogs and cats during general anaesthesia. Fifteen clinical studies met the inclusion criteria in this systematic review. In thirteen studies the population was dogs, while in two studies the population was cats. In the meta-analysis, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
(152 reference statements)
0
2
0
Order By: Relevance
“…Regarding preanaesthetic preparation of the animals, the fasting time reportedly ranged from 12 to 24 hours. While 12‐hour fasting is commonly reported in domestic cats, 24 hours may be regarded as a relatively long time 17–19 . However, this may be necessary to allow gastric emptying in large feline species after a large meal; moreover, one study conducted on domestic cats showed that total gastrointestinal transit time may be even longer than 46 hours in senior cats, although younger cats tended to show quicker emptying times 20 …”
Section: Discussionmentioning
confidence: 99%
“…Regarding preanaesthetic preparation of the animals, the fasting time reportedly ranged from 12 to 24 hours. While 12‐hour fasting is commonly reported in domestic cats, 24 hours may be regarded as a relatively long time 17–19 . However, this may be necessary to allow gastric emptying in large feline species after a large meal; moreover, one study conducted on domestic cats showed that total gastrointestinal transit time may be even longer than 46 hours in senior cats, although younger cats tended to show quicker emptying times 20 …”
Section: Discussionmentioning
confidence: 99%
“…The benefit of diode laser therapy does not outweigh the risks associated with additional anesthetic occasions at this time. [37][38][39] This study's most notable limitation is the lack of data describing RP/C as a monotherapy to compare with these results. A control group within the same facility was not available retrospectively within the same period (2017-2020).…”
Section: Discussionmentioning
confidence: 99%